Divorce for Lack of Spending in the Algerian Family Law - Hicham, Debih (Journal of Legal Studies and Researches, 2021)
This research paper deals with one of the issues of the family relationship, which is breaking the marital bond at the request of the wife by way of divorce, as the Algerian legislator listed ten reasons so that the wife can request divorce The first reason is divorce due to the husband’s refusal to spend on his wife and refraining from presenting it is a harm to the wife. For lack of spending and the measures taken about it, and some problems related to divorce for lack of spending and the proposed solutions to them.